PENGARUH MEDIA FLASHCARD TERHADAP KEMAMPUAN KOGNITIF ANAK USIA 3-4 TAHUN DI TPA YAYASAN PANTISILA PAUD SANTO RAFAEL SINGARAJA - Mochamad Heri; Putu Agus Ariana (STIKes Buleleng, 2018)
Introduction: Cognitive ability is a process of thinking, namely the ability of individuals to connect, assess, and consider an event or event. Flashcard media is a medium of learning in the form of picture cards measuring 25x30 cm. The purpose of this study was to determine the effect of flashcard media towards the cognitive abilities of children aged 3-4 years at TPA Foundations Pantisila Paud Santo Rafael Singaraja. Methods: The design research was pre-experimental with one group pre-post test design. The population used in this study were children aged 3-4 years at TPA Foundations Pantisila Paud Santo Rafael Singaraja. Sample used 23 respondents who have been selected by using total sampling technique. Measurement of cognitive abilities were collected by using an observation sheet that is guided by the task of developmental task by age in Denver II. This research used paired sample t-test with significant level α = 0,05. Result: The results shows the average value (mean) of pre 43,83 and average value (mean) of post 60,87. The result of parametric statistic using paired sample t-test obtained pre and post results (0,000) <α (0,05), which mean H0 rejected and Ha accepted. Conclutions: This shows that there is influence of flashcard media towards cognitive ability of children aged 3-4 Years at TPA Foundations Pantisila Paud Santo Rafael Singaraja.